PENGARUH LITERASI KEUANGAN DAN SOCIAL MEDIA EXPOSURE TERHADAP KEPUTUSAN INVESTASI CRYPTOCURRENCY DI INDONESIA DENGAN CONFIDENCE SEBAGAI MEDIASI - Aji Kurniawan; Agus Prayitno; Dwi Eko Waluyo; Suhita Whini Setyahuni (Politeknik Negeri Ambon, 2026)
Introduction: This study aims to explore the effect of financial literacy and social media exposure on cryptocurrency investment decisions among Generation Z in Indonesia, with confidence serving as a mediating variable.Methods: This research applies a quantitative approach with an explanatory design. Data were collected via online questionnaires from 121 Generation Z respondents in Indonesia who have experience or interest in cryptocurrency investments, selected using purposive sampling. The data were then analyzed through Structural Equation Modeling based on Partial Least Squares (PLS-SEM) using SmartPLS software.Results: The statistical results indicate that both financial literacy and social media exposure have a positive and significant direct effect on cryptocurrency investment decisions. Furthermore, both independent variables significantly influence the formation of investors' confidence. In terms of mediation, confidence is proven to have a positive and significant effect on investment decisions and acts as a significant partial mediator in bridging financial literacy and social media exposure toward cryptocurrency investment decisions.Conclusion and suggestion: These findings suggest that investment choices in digital assets are shaped by an interaction of cognitive capacity, digital information environments, and psychological mechanisms as outlined in Behavioral Finance Theory. Future research is suggested to expand the respondent scope and incorporate other behavioral biases such as herding behavior or fear of missing out (FOMO). Keywords: Confidence, Financial Literacy, Investment Decision, Social Media Exposure, Generation Z